Using the Lakatosian Conflict Map for conceptual change of pre-service elementary teachers about the seasons. Issue 1 (2nd January 2017) - Oh, Jun-Young; Lee, Hyonyong; Lee, Sung-Soon
Abstract: Background: Kuhn's model of science has been widely influential, but in this paper, it is argued that it is more appropriate to consider constructivist learning within science education as a research program in the sense used by Lakatos. Purpose/Hypothesis: This study offers teaching strategies and their corresponding instructional sequences based on Lakatosian Methodology, and examines the effects of a Lakatosian Conflict Map using pre-service elementary teachers' conceptual understandings of the causes of seasons. Design/Method: The Lakatosian Conflict Map was applied to concepts of seasonal change held by pre-service elementary teachers. Results: Most pre-service elementary teachers consistently protect their hard-core beliefs about seasonal change by offering auxiliary hypotheses related to earth's elliptical orbit and the tilt of its rotational axis in response to activities designed to promote conceptual change around knowledge related to the cause of the seasons. Specifically, the critical event rather than the discrepant event in the Lakatosian Conflict Map was conducted in a Lakatosian conflict group and these students were allowed to explicitly express their representations about the phenomena derived from these events. The result of this study is that instruction using the new Lakatosian Conflict Map produced more favorable outcomes in terms of conceptual change than traditional instruction. Conclusions: This research concludes that the Lakatosian Conflict Map can help science teachers and students resolve the conflicts between students' existing ideas and target scientific concepts.